Characteristics of a single-layer graphene field effect transistor with UV/ozone treatment - Tran, Xuan Anh (2013)
The performance of a single-layer graphene field effect transistor treated with UV/ozone at various temperatures is studied. It is observed that the number of the defects in graphene sheet increases with the UV/ozone treatment time, evidenced by Raman spectra. Moreover, the UV/ozone treatment dopes graphene into p-type as the time increases, which is consistent with the electric transfer measurements. With the increase in the UV/ozone treatment time, the mobility of graphene transistor degrades, and the degradation accelerates with the increase in temperature. We further verified by XPS measurement that the oxygen related carbon group O=C-O formation is the main cause for the mobility degradation.